First report of a carbapenemase gene blaOXA-181 harbored in a conjugative plasmid in Kluyvera sichuanensis isolated from spinach - Xu Yang; Jinkyung Kim; Nhu-Y Do; Xinhui Li; En Huang; Se-Ran Jun; Sun Hee Moon; Erin L. DiCaprio; Shuting Chen (International Journal of Food Microbiology, 2026)

Assessing the effectiveness of phosphine fumigation and cold treatment for controlling Carposina sasakii on apples - Hwee-Seung Ji; Asmar Soleymanzadeh; Jun-Ran Kim; Min-Goo Park (Journal of Stored Products Research, 2026)

Comprehensive analyses of carbapenem-resistant and ESBL-producing bacteria in fresh vegetables and their resistome in the United States - Sun Hee Moon; Xu Yang; Jinkyung Kim; Elizabeth Leighton; Se-Ran Jun; Erin DiCaprio; Chelsea Gale; Shuting Chen; Xinhui Li; En Huang (Food Research International, 2026)

Suppressing microRNA396 activity enhances regeneration efficiency of viable shoots from cotyledon explants in pepper - Min Jun Shin; Seong Sub Ku; Su-Jin Park; Sang Un Park; Sung Ran Min; Hyun-Soon Kim; Hyo-Jun Lee (Plant Biotechnology Reports, 2026)

Enhanced fumigant toxicity of methyl benzoate and phosphine combination against phosphine-resistant Rhyzopertha dominica (Fabricius) (Coleoptera: Bostrichidae) - Hwal-Su Hwang; Md Munir Mostafiz; Jun-Ran Kim; Bong-Su Kim; Soo-Jung Suh; Jinmo Koo; Kyeong-Yeoll Lee (Journal of Stored Products Research, 2026)

Synergistic toxicity assessment of ethyl formate combined with low-oxygen and cold treatments against the red flour beetle, Tribolium castaneum Herbst - Jae-Ho Ban; Jin-Sung Yoo; Ji-Eun Choi; Jun-Ran Kim; Bong-Su Kim (Journal of Stored Products Research, 2026)

Multistrain Probiotics Alleviate Diarrhea by Modulating Microbiome-Derived Metabolites and Serotonin Pathway - Jin-Ju Jeong; Yoo-Jeong Jin; Raja Ganesan; Hee Jin Park; Byeong Hyun Min; Min Kyo Jeong; Sang Jun Yoon; Mi Ran Choi; Satya Priya Sharma; You Jin Jang; Uigi Min; Jong-Hyun Lim; et al. (Probiotics and Antimicrobial Proteins, 2025)
Diarrhea, a common gastrointestinal symptom in health problems, is highly associated with gut dysbiosis. The purpose of this study is to demonstrate the effect of multistrain probiotics (Sensi-Biome) on diarrhea from the perspective of the microbiome-neuron axis. Sensi-Biome ( Lactiplantibacillus plantarum , Bifidobacterium animalis subsp. lactis , Lactobacillus acidophilus , Streptococcus thermophilus , Bifidobacterium bifidum , and Lactococcus lactis ) was administered in a 4% acetic acid–induced diarrhea rat model at concentrations of 1 × 10 8 (G1), 1 × 10 9 (G2), and 1 × 10 10 CFU/0.5 mL (G3). Diarrhea-related parameters, inflammation-related cytokines, and stool microbiota analysis by 16S rRNA were evaluated. A targeted and untargeted metabolomics approach was used to analyze the cecum samples using liquid chromatography and orbitrap mass spectrometry. The stool moisture content ( p < 0.001), intestinal movement rate ( p < 0.05), and pH ( p < 0.05) were significantly recovered in G3. Serotonin levels were decreased in the multistrain probiotics groups. The inflammatory cytokines, serotonin, and tryptophan hydroxylase expression were improved in the Sensi-Biome groups. At the phylum level, Sensi-Biome showed the highest relative abundance of Firmicutes . Short-chain fatty acids including butyrate, iso-butyrate, propionate, and iso-valeric acid were significantly modified in the Sensi-Biome groups. Equol and oleamide were significantly improved in the multistrain probiotics groups. In conclusion, Sensi-Biome effectively controls diarrhea by modulating metabolites and the serotonin pathway.

Transcriptomic insights into detoxification and mitochondrial responses of Tribolium castaneum (Coleoptera: Tenebrionidae) to carbonyl sulfide exposure - Na-Ri Shin; Rashmi Manohar Mahalle; Jun-Ran Kim; Bong-Su Kim; Keon Mook Seong (Journal of Stored Products Research, 2025)

Quinine inhibits myogenic differentiation by disrupting AKT signaling pathway - Mi Ran Byun; Sou Hyun Kim; RanJu Woo; Seung Jun Noh; Sang Hoon Joo; Young-Suk Jung; Joon-Seok Choi (Toxicological Research, 2025)

Rocaglamide-A mitigates LPS-induced hepatic inflammation by modulating JNK/AP-1 signaling cascade and ROS production in hepatocytes - Yoon-su Ha; Taek-Kyong Kim; Jun Heo; Jintaek Oh; Seung-Kyoon Kim; Jeongkyu Kim; Jeonghyung Lee; Se-Ran Yang; Seonghwan Hwang; Seung-Jin Kim (Toxicological Research, 2025)

Accelerating ionic–electronic percolation pathways via catecholate coordination of bioinspired-polymer dopamine in all-solid-state composite cathode - Thuy Hoai Linh Vuong; Naila Riaz Mastoi; Jae Seok Nam; Weerawat To A Ran; Cheayeon Ha; Min-Sik Park; Young-Jun Kim (Chemical Engineering Journal, 2024)

Flexural properties of ultra-high performance fiber reinforced concrete based on three-dimensional random distribution of steel fibers - Ya Lu; Jingcheng Han; Puyan Wang; Xiangguo Wu; Hyeon-Jong Hwang; Jian Zhou; Ran Li; Sung-Hyun Kim; Ho-Jun Lee (Engineering Structures, 2023)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Correction to: Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2023)

Multiple low-dose radiation-induced neuronal cysteine transporter expression and oxidative stress are rescued by N-acetylcysteine in neuronal SH-SY5Y cells - Ji-Young Yoo; Ye-Ji Lee; Yu-Jin Kim; Tai-Kyoung Baik; Jun-Ho Lee; Mi‑Jo Lee; Ran-Sook Woo (NeuroToxicology, 2023)

Phosphine gas in the dark induces severe phytotoxicity in Arabidopsis thaliana by increasing a hypoxia stress response and disrupting the energy metabolism: Transcriptomic approaches - Kyeongnam Kim; Chaeeun Kim; Jinsung Yoo; Jun-Ran Kim; Yoon-Ha Kim; Sung-Eun Lee (Journal of Hazardous Materials, 2023)

Correction to: A single amino acid insertion in LCYB2 deflects carotenoid biosynthesis in red carrot - Seung Hee Jo; Hyun Ji Park; Areum Lee; Haemyeong Jung; Sung Ran Min; Hyo-Jun Lee; Hyun-Soon Kim; Min Jung; Ji Young Hyun; Youn-Sung Kim; Hye Sun Cho (Plant Cell Reports, 2022)

Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2022)
The strawberry growth and fruit yield of five Korean cultivars in the tunnel-type greenhouse predicted using their growth. The number of leaves, petiole length, leaf length and width, crown diameter, and the ratio of red and far-red (RFR) of the five Korean cultivars were measured during the cultivation period. The number of leaves of all cultivars exhibited a similar trend during this period; the plant and petiole length of ‘Maehyang’ were the longest, leaf length exhibited similar trends in all five cultivars except for ‘Jukhyang’, the leaf width of ‘Arihyang’, was the longest, and crown diameter of ‘Keumsil’ was the thickest. The leaf length, crown diameter, and RFR were associated with the fruit yield in the multiple linear regression. When a single model was used to predict the yield of all five cultivars, the correlation between expected yield and actual yield was r = 0.53. When cultivar-specific models were built for the prediction, the correlation increased to r = 0.77. The results indicated that the fruit yield of strawberry cultivars could be better predicted by considering cultivar-specific information, so it may be necessary to consider individual cultivars specifically rather than all cultivars simultaneously.

Radiological Investigation of Gas Embolism in the East Asian Finless Porpoise (Neophocaena asiaeorientalis sunameri) - Adams Hei Long Yuen; Sang Wha Kim; Sung Bin Lee; Seyoung Lee; Young Ran Lee; Sun Min Kim; Cherry Tsz Ching Poon; Jun Kwon; Won Joon Jung; Sib Sankar Giri; Sang Guen Kim; Jeong Woo Kang; et al. (Frontiers in Marine Science, 2022)
Cetaceans have long been considered biologically adapted to suffer no adverse effects from diving-related tissue gas tension. However, increasing reports of gas embolism in cetaceans inhabiting European, Mediterranean and American waters have challenged the conventional understanding of marine mammal diving physiology. In human hyperbaric medicine, virtopsy techniques such as post-mortem computed tomography (PMCT) facilitate the visualization of gas embolism and could be performed adjunct to conventional autopsy. This research presents the first case of gas embolism identified in an East Asian finless porpoise inhabiting Asian waters. Massive gas embolic lesions were found in the liver, which had been compressing both the lungs and abdominal organs, and signs of pneumonia and parasitic infection were observed in both lungs. It is hypothesized that this porpoise might have been unable to expel in vivo gas bubbles from its circulation due to pulmonary dysfunction. Consequently, gas bubbles agglomerated in the liver, resulting in the development of gas embolic lesions. The findings of the present study provide insights into the occurrence of gas embolism in the East Asian finless porpoise, highlighting the potential of PMCT as a promising tool for the diagnosis of gas embolism in stranded cetaceans.

A single amino acid insertion in LCYB2 deflects carotenoid biosynthesis in red carrot - Seung Hee Jo; Hyun Ji Park; Areum Lee; Haemyeong Jung; Sung Ran Min; Hyo-Jun Lee; Hyun-Soon Kim; Min Jung; Ji Young Hyun; Youn-Sung Kim; Hye Sun Cho (Plant Cell Reports, 2021)

Poor outcomes of early recurrent post-transplant bloodstream infection in living-donor liver transplant recipients - Si-Ho Kim; Seok Jun Mun; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Gyu-Seong Choi; Jong Man Kim; Jae-Won Joh; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Land-cover changes and distribution of wetland species in small valley habitats that developed in a Late Pleistocene middle terrace region - Ji Yoon Kim; Yuna Hirano; Hiroki Kato; Akira Noda; Ran-Young Im; Jun Nishihiro (Wetlands Ecology and Management, 2020)

Neuregulin1 Attenuates H2O2-Induced Reductions in EAAC1 Protein Levels and Reduces H2O2-Induced Oxidative Stress - Jun-Ho Lee; Ji-Young Yoo; Han-byeol Kim; Hong-Il Yoo; Dae-Yong Song; Sun Seek Min; Tai-Kyoung Baik; Ran-Sook Woo (Neurotoxicity Research, 2019)

Zinc Oxide Nanoparticles Exhibit Both Cyclooxygenase- and Lipoxygenase-Mediated Apoptosis in Human Bone Marrow-Derived Mesenchymal Stem Cells - Dong-Yung Kim; Jun-Hyung Kim; Jae-Chul Lee; Moo-Ho Won; Se-Ran Yang; Hyoung-Chun Kim; Myung-Bok Wie (Toxicological Research, 2019)

Metformin Inhibits the Development of l-DOPA-Induced Dyskinesia in a Murine Model of Parkinson’s Disease - Young-Kyoung Ryu; Hye-Yeon Park; Jun Go; Dong-Hee Choi; Yong-Hoon Kim; Jung Hwan Hwang; Jung-Ran Noh; Tae Geol Lee; Chul-Ho Lee; Kyoung-Shim Kim (Molecular Neurobiology, 2018)

Toxicity of Juniperus oxycedrus oil constituents and related compounds and the efficacy of oil spray formulations to Dermatophagoides farinae (Acari: Pyroglyphidae) - Jun-Ran Kim; Haribalan Perumalsamy; He Min Shin; Sang-Guei Lee; Young-Joon Ahn (Experimental and Applied Acarology, 2017)

Complete mitochondrial genome of the beluga whale Delphinapterus leucas (Cetacea: Monodontidae) - Ji Hyung Kim; Young-Ran Lee; Jeong-Rack Koh; Jin Woo Jun; Sib Sankar Giri; Hyoun Joong Kim; Cheng Chi; Saekil Yun; Sang Geun Kim; Sang Wha Kim; Hye Kwon Kim; Dae Gwin Jeong; et al. (Conservation Genetics Resources, 2017)

Study of Photo and Thermoluminescence Properties to Identify Irradiated Dried-Fishery Products - Moon-Young Kim; Jae-Jun Ahn; Kashif Akram; Gui-Ran Kim; Mi-Seon Jeong; Ji-Young Kwak; Joong-Ho Kwon (Journal of Aquatic Food Product Technology, 2016)

Acaricidal activity of Asarum heterotropoides root-derived compounds and hydrodistillate constitutes toward Dermanyssus gallinae (Mesostigmata: Dermanyssidae) - Jun-Ran Kim; Haribalan Perumalsamy; Ju-Hee Lee; Young-Joon Ahn; Young Su Lee; Sang-Guie Lee (Experimental and Applied Acarology, 2016)

Toxicity assessment of a novel silk fibroin and poly-methyl-methacrylate composite material - Min Ju Chae; Dae Won Kim; Yun Joong Kim; Hae Yong Kweon; Yong-Jun Cho; Soo Young Choi; Hae Ran Lee (Molecular & Cellular Toxicology, 2014)

SPARC is involved in the maintenance of mitotically inactivated mouse embryonic fibroblast cells - Jun Yeon Won; Young Jin Lee; Seung-Joon Lee; Woo Jin Kim; Seon-Sook Han; Se-Ran Yang; Heung-Myong Woo; Sung-Min Park; Hyang-Ah Lee; Seok-Ho Hong (In Vitro Cellular & Developmental Biology - Animal, 2013)

Molecular characterization of KGH, the first human isolate of rabies virus in Korea - Jun-Sun Park; Chi-Kyeong Kim; Su Yeon Kim; Young Ran Ju (Virus Genes, 2013)

Identification and characterization of class I chitinase in Panax ginseng C. A. Meyer - Rama Krishna Pulla; Ok Ran Lee; Jun-Gyo In; Shohana Parvin; Yu-Jin Kim; Ju-Sun Shim; Hua Sun; Yeon-Ju Kim; Kalaiselvi Senthil; Deok-Chun Yang (Molecular Biology Reports, 2011)

Identification and characterization of chlorpyrifos-methyl and 3,5,6-trichloro-2-pyridinol degrading Burkholderia sp. strain KR100 - Jun-Ran Kim; Young-Joon Ahn (Biodegradation, 2009)

Effect of food on systemic exposure to niflumic acid following postprandial administration of talniflumate - Wonku Kang; Kibum Kim; Eun-Young Kim; Kwang-il Kwon; Jun Seok Bang; Young-Ran Yoon (European Journal of Clinical Pharmacology, 2008)

Genetic transformation ofAjuga multiflora bunge withAgrobacterium rhizogenes and 20-hydroxyecdysone production in hairy roots - Ok Tae Kim; M. Manickavasagm; Young Jun Kim; Mei Ran Jin; Kwang Soo Kim; Nak Sul Seong; Baik Hwang (Journal of Plant Biology, 2005)

Anti-fungal effects of phenolic amides isolated from the root bark of Lycium chinense - Dong Gun Lee; Yoonkyung Park; Mi-Ran Kim; Hyun Jun Jung; Young Bae Seu; Kyung-Soo Hahm; Eun-Rhan Woo (Biotechnology Letters, 2004)

Characterization of antidepressant-like effects of p -synephrine stereoisomers - Kee-Won Kim; Hee-Doo Kim; Jun-Sub Jung; Ran-Sook Woo; Hee-Sung Kim; Hong-Won Suh; Yung-Hi Kim; Dong-Keun Song (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)